Interaction Between Internet Banking and Bank Performance: The Case of Europe - TUNAY, KAŞİF BATU; TUNAY, NECLA (ELSEVIER SCIENCE BV, 2015)
In this study, the interaction between internet banking and bank performance is investigated by panel causality tests. Banking data of 30 European countries analyzed by Demitrescu - Hurlin panel causality test for the period 2005-2013. ROA and ROE ratios were used as measures of bank performance. Not only whole sample consisting of Euro Area and the others but also Euro Area and the other countries in Europe considered as samples and tested two sub-samples. Results show that a strong relationship through internet banking to the bank performance in the Euro Area countries and for the rest of the Euro Area countries are also not determined causation significantly in both directions. On the other hand, there is also a significant relationship internet banking to performance of the bank considering the whole sample. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Internet banking; bank performance; panel casuality tests; HETEROGENEOUS PANELS